A secure edge power system based on a Docker container - Xu, Xinchen; Jiang, Yixin; Wen, Hong; Hou, Wenjing; Chen, Songlin (Frontiers in Energy Research, 2022)
With the advantages of low latency, high efficiency, and oneself-security, the edge computing paradigm is expected to widely be applied in a large number of scenarios. However, because the edge computing (EC) equipment is closer to various terminals in a realistic environment, it is also more vulnerable to terminal attacks. The security of edge computing equipment itself cannot be ignored. Docker is a lightweight container technology that highly fits the existing needs of edge computing with portability, security isolation, and convenience. In this paper, Docker technology is taken as the edge computing security support engine and a security monitoring system based on the Docker container is built. Meanwhile, combined with container monitoring and objective weighting method, a node security judgment method is proposed. Finally, according to the results of the node security evaluation, a method for evaluating the security of the unmonitored node is put forward. By this way, an edge computing security monitoring system based on the Docker container is built, and the wide performance under the real environment of the smart grid system is implemented to verify the proposed method. The results proved the efficiency security protection of the novel edge power system.